"Single-Man Technique". Issue 2 (June 2015) - Gupta, S.K. Venkatesh
<x xml:space="preserve">Abstract</x> Hemiarthroplasty is a clinically efficient and cost-effective procedure for varied indications of hip pathology, which allows for early weight-bearing and recovery among elderly population. As a part of reduction of prosthesis after its implantation, most surgeons follow conventional method of reduction. The conventional method of reduction of prosthesis needs an assistant to reduce the prosthesis and is often a laborious step that needs experience of the assisting staff and is usually associated with high chances of intraoperative periprosthetic fractures. To eliminate the learning curve and avoid the complications, we describe a new technique of reduction of prosthesis in hemiarthroplasty, wherein operating surgeon himself would reduce the prosthesis, thereby minimizing the effort of reduction. In the present study we compare the complications and results of 508 patients who underwent hemireplacement arthroplasty, in whom prosthesis was reduced using newly described single-man technique and conventional method of reduction.